The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fcell.2022.1044672
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mitochondrial dynamics and function in the retinal pigment epithelium by high-speed high-resolution live imaging

Abstract: Mitochondrial dysfunction is strongly implicated in neurodegenerative diseases including age-related macular degeneration (AMD), which causes irreversible blindness in over 50 million older adults worldwide. A key site of insult in AMD is the retinal pigment epithelium (RPE), a monolayer of postmitotic polarized cells that performs essential functions for photoreceptor health and vision. Recent studies from our group and others have identified several features of mitochondrial dysfunction in AMD including mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Given the early transcriptional changes in mitochondrial ROS metabolism, we decided to investigate mitochondrial dynamics and function by high-speed super-resolution live imaging of RPE explants from wildtype and Grn −/− mice 30 . Live imaging of MitoTracker-labeled mitochondria and volumetric reconstructions of mitochondrial networks showed increased connectivity or hyperfusion of mitochondria in 4-mo Grn −/− RPE that was even more pronounced in 17-mo mice (Figures 5A-5C).…”
Section: Resultsmentioning
confidence: 99%
“…Given the early transcriptional changes in mitochondrial ROS metabolism, we decided to investigate mitochondrial dynamics and function by high-speed super-resolution live imaging of RPE explants from wildtype and Grn −/− mice 30 . Live imaging of MitoTracker-labeled mitochondria and volumetric reconstructions of mitochondrial networks showed increased connectivity or hyperfusion of mitochondria in 4-mo Grn −/− RPE that was even more pronounced in 17-mo mice (Figures 5A-5C).…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the day after light onset, we found mitochondria redistributed away from the basal region of the cell towards the apical surface. Mitochondrial movement within the RPE has been studied in cell culture models by fluorescence microscopy but has not been shown in tissues at the resolution of electron microscopy that allows precise determination of apical vs. basal distribution [14,34,35]. The fixative used in electron microscopy can cause some sample shrinkage, but generally good preservation is maintained, as has been shown in correlative live cell imaging and electron microscopy studies [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mitochondrial movement and regions of close apposition between mitochondrial and other organelle membranes, known as membrane contact sites (MCSs), can likely aid in adapting and responding to changes in the local environment [12]. Previous studies including our work have shown that mammalian RPE is heavily populated with a heterogeneous population of mitochondria based on membrane potential and ATP production, and these mitochondria predominantly localize to the basal region of the cell [13][14][15].…”
Section: Introductionmentioning
confidence: 88%
“…Dysfunction in mitochondrial homeostasis, through abnormal dynamics and metabolic activities, represent a critical sign of advanced cellular age and may evolve into AMD [239]. Triggers related to AMD, such as tobacco smoking and complement activation, may induce mitochondrial fragmentation and dysfunction [240][241][242]. In addition, a state of hyperfusion, characterized by an abnormal increase of mitochondrial fusion, along with decreased mitochondrial turnover, has been identified as a driver of RPE senescence [162].…”
Section: Aging and Mitochondrial Dysfunctionmentioning
confidence: 99%